Pengaruh Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Belanja Modal dengan Pertumbuhan Ekonomi sebagai Variabel Moderasi di Kota Langsa - Tuti Meutia; Imelda Husna; Afrah Junita (Jurnal Transformasi Administrasi, 2022)
This research was conducted to know the effect of the General Allocation Fund and the Special Allocation Fund on Capital Expenditures with Economic Growth as a Moderating variable. The results of this study indicate that: (1) General Allocation Funds have a positive and significant effect on Capital Expenditures (2) Special Allocation Funds have a positive and significant effect on Capital Expenditures (3) General Allocation Funds have no significant effect on Capital Expenditures with Economic Growth as a Moderating variable (4) Special Allocation Funds have a positive and significant effect on Capital Expenditures with Economic Growth as a Moderating variable (5) General Allocation Funds and Special Allocation Funds have a positive and significant effect on Capital Expenditures (6) General Allocation Funds and the Special Allocation Fund has a positive and significant effect on Capital Expenditure with Economic Growth as a Moderating variable.